Pengaruh Struktur Modal, Persistensi Laba dan Ukuran Perusahaan Terhadap Kualitas Laba - Anastasia Lie Tjahjadi; Dade Nurdiniah (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This research was aimed to know determine the effect of capital structure, earnings persistence and company size on earnings quality. Earnings quality is a measure to compare what the profit generated is the same as what was previously planned. In this study, the sample used was manufacturing companies listed on the Indonesia Stock Exchange in the 2016-2018 period with a total sample of 58 companies. Data analysis method used in this study uses multiple linear regression analysis. The results showed that the capital structure affects earnings quality. The persistence of earnings based on accrual quality is stated to have an effect on earnings quality. The size of the company stated no effect on earnings quality.